IFN-α/IFN-λ responses to respiratory viruses in paediatric asthma. Issue 3 (30th March 2017) - Bergauer, Annika; Sopel, Nina; Kroß, Bettina; Vuorinen, Tytti; Xepapadaki, Paraskevi; Weiss, Scott T.; Blau, Ashley; Sharma, Himanshu; Kraus, Cornelia; Springel, Rebekka; Rauh, Manfred; Mittler, Susanne; et al.
The letter by S. Baraldo and co-workers raises some interesting points. It is correct that we cannot exclude the possibility that interferon upregulation during the acute phase in asthmatics, though existent, is suboptimal if compared to healthy subjects. It is also possible that there might be differences in kinetics, with peak expression reached at different time points in different groups. What we have established is that interferon deficiency in asthma is more complex than a simple on/off mechanism. Analysis of acute infections that cause asthma exacerbation should be included in future studies http://ow.ly/GKcM309Gi9R